If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -2c = 2 Solving 6b + -2c = 2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2c' to each side of the equation. 6b + -2c + 2c = 2 + 2c Combine like terms: -2c + 2c = 0 6b + 0 = 2 + 2c 6b = 2 + 2c Divide each side by '6'. b = 0.3333333333 + 0.3333333333c Simplifying b = 0.3333333333 + 0.3333333333c
| -c+(c+a)=(-c+c)+a | | 6x(3-4x)=92 | | (9)+(-7)= | | 6x+(3+4x)=92 | | 2x-5+8=8x+10+32 | | 7x+1-3=-5 | | 1+8(7x+3)=-255 | | 18=4s | | -12x-17=-89o | | -4=3(x+8)+6x | | 3x-9=-20 | | 92+4x=3+6x | | -9(b+1)+4=3(2b-7)-b | | -2p+6p=24 | | 5b+11c=A | | 48=6x+1y | | 6m-2=m-6+m-12 | | 6.9e+13= | | 48=7x+1y | | 3x-4+9x=3(3x+4)+36 | | 6y-15y-19=-91 | | 48=7x | | 5x+15=5x-19 | | 6x(4x+3)=92 | | 6x+(4x+3)=92 | | 7x+1-3=5 | | (3+3)4=24 | | 9x+12=4x-10 | | 12y^3=0 | | 4+5=187 | | 3+(4x+6x)=92 | | 7=4y+43+2y |